Biscogniauxia (Hypoxylon) Canker or Dieback in Trees - Claudia Paez; Jason A. Smith (EDIS)
Biscogniauxia canker or dieback (formerly called Hypoxylon canker or dieback) is a common contributor to poor health and decay in a wide range of tree species (Balbalian & Henn 2014). This disease is caused by several species of fungi in the genus Biscogniauxia (formerly Hypoxylon). B. atropunctata or B. mediterranea are usually the species found on Quercus spp. and other hosts in Florida, affecting trees growing in many different habitats, such as forests, parks, green spaces and urban areas (McBride & Appel, 2009).